Functional-stylistic potential of folk-colloquial idioms in M. Grushevskyi’s journalism (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with study of idiomatic structure of M.Grushevskyi’s journalistic heritage; the idioms of folk-colloquial origin were analysed, the status of their stylistic and pragmatic potential was defined.
Keywords: idiom; folk-colloquial phraseology; colloquial every day idiom, proverb; stylistic function; pragmatic effect